1991
DOI: 10.1161/01.cir.84.3.1157
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral vasoconstriction during head-upright tilt-induced vasovagal syncope. A paradoxic and unexpected response.

Abstract: BACKGROUND To determine the effect of vasovagally mediated syncope on the cerebral circulation, transcranial Doppler sonography was used to assess changes in cerebral blood flow velocity during head-upright tilt-induced syncope. METHODS AND RESULTS Thirty patients (17 men and 13 women; mean age, 43 +/- 22 years) with recurrent unexplained syncope were evaluated by use of an upright tilt-table test for 30 minutes, with or without an infusion of intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
121
4
2

Year Published

1992
1992
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(143 citation statements)
references
References 27 publications
16
121
4
2
Order By: Relevance
“…Altered cerebrovascular control unrelated to changes in PET CO 2 has been reported during LBNP following bed rest (44) and parabolic flight (38). In addition, a paradoxical cerebral vasoconstriction in healthy (5,6,22,38) and orthostatically intolerant (13,14) individuals has been reported during postural stress and LBNP. However, our previous work (38), as well as that of others (8,21), showed that cerebral autoregulation remains intact during HUT in healthy subjects, suggesting that decreases in perfusion pressure were unlikely to be the cause of the decrease in cerebral flow.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Altered cerebrovascular control unrelated to changes in PET CO 2 has been reported during LBNP following bed rest (44) and parabolic flight (38). In addition, a paradoxical cerebral vasoconstriction in healthy (5,6,22,38) and orthostatically intolerant (13,14) individuals has been reported during postural stress and LBNP. However, our previous work (38), as well as that of others (8,21), showed that cerebral autoregulation remains intact during HUT in healthy subjects, suggesting that decreases in perfusion pressure were unlikely to be the cause of the decrease in cerebral flow.…”
Section: Discussionmentioning
confidence: 98%
“…CFV MCA has been found to decrease with upright tilt (13,17,27,38) and lower body negative pressure (LBNP) (6,22). Concomitant with this decrease in CBF is a drop in PET CO 2 (6,17,22,27,38).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] Blood flow velocities (systolic, diastolic, and mean velocities) and the pulsatility and resistive indexes, which derive from the flow velocities, are the most common measurements used. Blood flow velocity increases and the pulsatility and resistive index decrease with arteriolar vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…Blood flow velocity increases and the pulsatility and resistive index decrease with arteriolar vasoconstriction. 16,17 The middle cerebral artery, which is frequently insonated under angles of less than 30°and which also supplies blood to approximately 85% of the hemisphere, 16 is the most common intracranial vessel used for transcranial Doppler ultrasonography. There are many studies which show that blood flow velocity and HEPATOLOGY Vol.…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, it has been shown that vasodilatation occurs in muscle vascular beds during vasodepressor syncope, but vasoconstriction may develop in skin 24 and brain. 25 In the study of baroreceptors, it has been demonstrated that reflex control of HR and vascular resistance may be quantitatively dissociated. 26 Thus, the differences of HR and vascular resistance between patients with vasovagal and vasodepressor syncope represent the difference in vagal activation and discrepancy in sympathetic inhibition in the peripheral vascular system.…”
Section: Discussionmentioning
confidence: 99%